Assessing Constraints in Pratapdhan Backyard Poultry Farming: A Study of Farmers in Udaipur, Rajasthan, India - Meenu,; , Ananda K R; , Shivani Singh; , Preeti Y H; , Ankit Pal (Archives of Current Research International, 2025)
Poultry farming is critical for the development of the economy. It usually has better returns than other livestock activities in developing countries. The study assessed the constraints of backyard poultry farmers in Udaipur district, Rajasthan, focusing on the Pratapdhan breed under the All India Coordinated Research Project (AICRP) conducted in 2022-23 across four villages from Girwa and Gogunda tehsils, data from 120 farmers revealed that 74.17 per cent of the beneficiary farmers had medium level of constraints faced by respondents, while 13.33% and 12.50% had low and high constraints faced by respondents, respectively. In Gogunda tehsil, 75.00% had medium faced constraints, compared to 73.68% in Girwa. The study underscores the importance of targeted training and exposure to improve poultry management and promote sustainable practices in rural areas.